State of the art of solid-state transformers: Advanced topologies, implementation issues, recent progress and improvements - Hannan M.A.; Ker P.J.; Lipu M.S.H.; Choi Z.H.; Rahman M.S.A.; Muttaqi K.M.; Blaabjerg F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Power converters; Topology; Control operations; Converter controls; Different voltages; Emerging technologies; Issues and challenges; Potential benefits; Power distributions; Solid state transformer (SST); Power control